Bezpośrednie inwestycje zagraniczne w dobie integracji - wybrane problemy - Markowska-Przybyła, Urszula (Foreign Direct Investments in a Period of Integration - Selected Problems, 2007)
The basic problems connected with foreign direct investments have been presented in the article. There have been presented positive favourable and unfavourable possibilities of influence FDI on host-country economies, the value of inflow FDI to Poland on the world and countries of Central-East European background, as well as level and regional diversity of inflow FDI to Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 231-246